In vitro antibacterial effect of Stevia rebaudiana extract on Streptococcus sanguinis and Actinomyces viscosus, starter bacterias in dental biofilm formation - Brañez Reyes, Katherine (2018)
Objective: To determine the antibacterial effect of Stevia rebaudiana extract (S. rebaudiana) against Streptococcus sanguinis (S. sanguinis) and Actinomyces viscosus (A. viscosus). Methods: The plaque agar sensitivity test was developed with discs, for which strains of S. sanguinis and A. viscosus were grown on trypticase soy agar plates (TSA) and blood agar, respectively, incubating at 37 °C. for 48 hours to S. sanguinis and for 7 days under conditions of anaerobiosis to A. viscosus. The bacterial strains were standardized at a scale of 0.5 of Mc Farland, and taking inocula of 100 μL were seeded in ten plates of blood agar and TSA, then in each plate were placed discs of 6 mm diameter in equidistant form, loaded with 10 μL of different concentrations of the extract, to incubate. Results: The concentrations of 15, 30, 50, 60 and 120 mg/ml presented an average inhibition halo of 6.8±0.258; 8.2±1.15; 8.2±1.13; 8.3±0.823; 8.1±0.80 mm respectively, for the bacterium S. sanguinis. The concentrations of 15, 30, 50, 60 and 120 mg/ml showed an average inhibition halo of 7.2±0.75; 9.65±2.15; 9.20±2.03; 7.95±1.09; 8.05±0.96 mm respectively, for the bacterium A. viscosus. The Kruskal Wallis test determined that there is a statistically significant difference with p<0.05 of the averages between the concentrations of A. viscosus. Conclusions: The extract of S. rebaudiana does not have an antibacterial effect for S. sanguinis, but has an antibacterial effect on A. viscosus for concentrations of 30 and 50 mg/ml.